2013
DOI: 10.1093/carcin/bgt410
|View full text |Cite
|
Sign up to set email alerts
|

The stem cell factor SOX2 regulates the tumorigenic potential in human gastric cancer cells

Abstract: Gastric cancer (GC) is still one of the most common causes of cancer-related death worldwide, which is mainly attributable to late diagnosis and poor treatment options. Infection with Helicobacter pylori, different environmental factors and genetic alterations are known to influence the risk of developing gastric tumors. However, the molecular mechanisms involved in gastric carcinogenesis are still not fully understood, making it difficult to design targeted therapeutic approaches. Aberrant expression of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 47 publications
5
66
1
1
Order By: Relevance
“…Histopathologically, the transplanted hGICs with miR340 overexpression showed apoptosis in the early stage of transplantation, suggesting that antitumorigenic effects of miR340 in GIC might be partly due to tumor cell apoptosis. Recently, the inhibition of Sox2, which is a stem cell marker, was demonstrated to reduce the tumorigenic potential of human gastric cancer cells (25). In the glioma cell lines, the expression levels of Sox2 were initially quite low; therefore, Sox2 function was likely not highly affected by miR340 in these cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, the transplanted hGICs with miR340 overexpression showed apoptosis in the early stage of transplantation, suggesting that antitumorigenic effects of miR340 in GIC might be partly due to tumor cell apoptosis. Recently, the inhibition of Sox2, which is a stem cell marker, was demonstrated to reduce the tumorigenic potential of human gastric cancer cells (25). In the glioma cell lines, the expression levels of Sox2 were initially quite low; therefore, Sox2 function was likely not highly affected by miR340 in these cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SOX2 is also confusing, in part because its expression is reduced in some gastric cancers and increased in others. Adding to the uncertainty, SOX2 overexpression in some gastric cancer lines arrests cell replication and induces apoptosis (Otsubo et al, 2008) but inhibition of SOX2 has similar effects in the AZ-521 human gastric cancer cell line (Hutz et al, 2014). The significance of many of these associations is unclear, leaving much to learn about the relationship between developmental regulation and adult gastric disorders.…”
Section: Common Congenital and Acquired Adult Stomach Disordersmentioning
confidence: 99%
“…Interestingly, strong SOX2 expression is associated with many types of human solid tumors, including lung cancer, breast cancer, ovarian carcinoma, pancreatic carcinoma and esophageal carcinoma [7] . Furthermore, recent studies have shown that SOX2 is involved in the biological behaviors of a variety of human malignancies, including proliferation [8] , apoptosis [9,10] , and invasion and metastasis [7] . In terms of CRC, the increased expression of SOX2 is associated with distant metastases and lymph-node metastases in rightsided CRC [11] .…”
Section: Introductionmentioning
confidence: 99%